(3GdJOQjH h JfejI GdehGQO GdHTQjI (B:s (3GdCSSS h GdYedjGJ (B/s - (3YSGa, YHO GdeYWj eMeOs; (3MeOGf, jYbhH s ((3YeGf(B: s (3OGQ RgQGf(B, s, 2009)
(3GdJOQjH h GdJfejI , CSGSjGJ GdJOQjH , JMOjO GdGMJjGLGJ GdJOQjHjI h GdGSGdjH GdJOQjHjI , GdeYjfGJ Ch GdeSGYOGJ GdJOQjHjI h GdMbGFH GdJOQjHjI , fXGe GdJOQjH h GdYedjI GdJOQjHjIs
(3agQS GdGTcGd U(B.3 (3; agQS GdLOGhd U(B.5s
Keywords: (3EOGQI GdCaQGOs; (3GdJOQjH Gdegfjs; (3GdJfejIs; (3GdehGQO GdHTQjIs